2021
DOI: 10.1186/s12884-021-03633-8
|View full text |Cite
|
Sign up to set email alerts
|

Beyond counting induced abortions, miscarriages and stillbirths to understanding their risk factors: analysis of the 2017 Ghana maternal health survey

Abstract: Background Inasmuch as induced abortions, miscarriages and stillbirths constitute common adverse pregnancy outcomes contributing to poor maternal health, there is paucity of literature about these in Ghana. We investigated the factors associated with induced abortions, miscarriages and stillbirths in Ghana. Methods Data derived from the 2017 Ghana Maternal Health Survey was used in this study. Women aged 15–49 constituted the target for the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…On the contrary, the current study's ndings contradict those of an Ethiopian study, which showed a signi cant association between women's employment status and abortion [22]. It was found that the probability of pregnancy termination was less likely to occur among unemployed women compared to their employed counterparts [20].…”
Section: Discussioncontrasting
confidence: 99%
“…On the contrary, the current study's ndings contradict those of an Ethiopian study, which showed a signi cant association between women's employment status and abortion [22]. It was found that the probability of pregnancy termination was less likely to occur among unemployed women compared to their employed counterparts [20].…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, AGYW in most countries in SSA are often denied access to family planning services due to negative socio-cultural norms and this increases their tendency of experiencing unintended pregnancies, which could end in abortion [21,22]. Apart from abortion, miscarriages and stillbirths, which also constitute other forms of pregnancy termination have been found to be higher among never married adolescent girls due to stigma, which affect their emotional and psychological health and low utilization of antenatal care services [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the two-stage sampling procedure exist in previous studies [12,13]. A total of 62, 747 AGYW (aged [15][16][17][18][19][20][21][22][23][24] were included in this study. Table 1 has comprehensive information on the sample.…”
Section: Sample and Sampling Strategymentioning
confidence: 99%
“…The pregnancy outcomes of secondary pregnancies are more favorable than that of primary pregnancies. The incidences of fetal growth restriction, fetal death, and low birth weight were lower in subsequent pregnancies 1 , 2 . Simultaneously, the incidence of preeclampsia (PE) and other complications associated with impaired fetal tolerance in multiparas were lower than those in nulliparas 3 , 4 .…”
Section: Introductionmentioning
confidence: 86%